Deleuze and the problem of affect - Cross, Donald J. S. (Plateaus., 2021)
D. J. S. Cross argues that Deleuze's ambivalence towards affect and embodiment have been overlooked because they only become apparent through a systematic analysis of affect throughout Deleuze's work. Cross outlines how Deleuze's system of thought both ruptures and complies with the tradition the recent 'affective turn' that hinges upon it.